Pengaruh The Effect of Green Coconut Water on Reducing Dysmenorrhea in Adolescents at the Raudlatul Ulum Tanggul Islamic Boarding School: The Effect of Green Coconut Water on Reducing Dysmenorrhea in Adolescents at the Raudlatul Ulum Tanggul Islamic Boarding School - Yuni Handayani, Yuni Handayani (Fetus : Journal of Midwifery, 2024)
Dysmenorrhea is pain or discomfort throughout the menstrual cycle. Dysmenorrhea is a normal complaint in women during menstruation. In Indonesia, 64.25% of adolescents experience dysmenorrhea. Dysmenorrhea pain can be managed with non-pharmacological therapies, one of which is green coconut water therapy. This therapy stimulates the body to stabilize prostaglandin production during menstruation and can then block the action of prostaglandins on uterine hypercontractions, thereby reducing dysmenorrhea. The aim was to determine the effect of green coconut water on reducing dysmenorrhea in adolescents at the Raudlatul Ulum Tanggul Islamic Boarding School. This research method used a pre-experimental design with a one-group pre-test-post-test design. The population in the study was 70 adolescents, with a sample of 41 adolescents using a simple random sampling technique. The results of statistical tests with Wilcoxon Test calculations using SPSS 23 obtained a p-value = 0.000 ≤ α = 0.05 which means there is an effect of giving green coconut water on reducing dysmenorrhea in adolescents at the Raudlatul Ulum Tanggul Islamic Boarding School. The conclusion is that there is an effect of giving green coconut water on reducing dysmenorrhea in adolescents at the Raudlatul Ulum Tanggul Islamic Boarding School. Suggestions are expected that every adolescent who experiences dysmenorrhea consumes green coconut water with a dose of 300 mg of magnesium so that the dysmenorrhea felt is reduced.